THE EFFECT OF KINESIOTAPE IN THE LOWER LIMB AREA ON IMPROVING LOCOMOTION IN PATIENTS WITH ISCHEMIC STROKE - Mariela Filipova; Daniela Popova (Peytchinski Publishing, 2023)
The aim of the study was to investigate the effect of Kinesiotape in the lower limb area on improving locomotion in patients with ischemic stroke. Materials and Methods: The study was conducted in the period 2014-2015 at the General Hospital for Active Treatment in Blagoevgrad. Forty patients were studied, divided into two groups of 20 patients - experimental (EG) and control group (KG). In addition, we have applied а standard kinesitherapy program in the two studied groups, in the experimental group, 3 kinesiotape tapes with a specific application "I" shape and a specialized method of application in the field of the foot and m. gluteus maximuswere placed. The results were compared with the results of the patients from the control group and processed with descriptive statistics, as well as non-parametric tests to prove statistically significant differences. Results: After research and analysis, we obtained faster recovery of locomotion in the experimental group and slowing of locomotor movements in the control group (Wilcoxon, ANOVA). Conclusion: The results of our research show that the application of the author's methodology with kinesiotape creates an opportunity to improve the functions in the damaged lower limb, improves locomotion and quality of life.